Lights of disenchantment: a study of Max Weber's thesis on the 'disenchantment of the world' from the perspective of visual studies. Issue 2 (3rd April 2019) - Loia, Donato
Abstract : At the end of 1917, during a conference at Munich University, the German sociologist Max Weber (1864–1920) made a bold announcement: 'The fate of our times is characterized by rationalization and intellectualization and, above all, by the "disenchantment of the world".' In this article, I provide an interpretation of the notion of 'disenchantment of the world.' Subsequently, I present visual material that might further illuminate Weber's idea. In the third part, I strictly concentrate my attention on one argument suggested by Weber: in 'disenchanted' societies 'mysterious incalculable forces do not come into play anymore.' Through two exemplary sculptures by the Danish artist Bertel Thorvaldsen (1770–1884), I continue my visual excursus on the 'disenchantment' thesis by connecting Weber's account on the intellectualisation of religious world-views with the autonomisation of the aesthetic sphere. The overall ambition of this article lies in providing an introductory account to an important intellectual problem and historical process through visual and textual analysis.